Assessment of Human Resource Development Platform for Visions about Future of Students University - Kunchai, Jetnipit (Interdisciplinary Academic and Research Journal, 2022)
The resulting impact contributes to enhancing the ability of higher education institutions to strengthen (hard-skills) and soft-skills and increase learning potential (high potential) for students and gain acceptance of the demands of the labor market. This is because the goals and objectives of the study is a quality education comprehensive equality and promote lifelong learning opportunities with the cutting edge of technology. Therefore, this research a survey of students who inspire to study co-operative education program and students need to go through the human resource development platform following to the standards of the Thai Cooperative Education Association 1) The learning in the course of preparing for co-operative education for 1 credit or more and 2) The training to prepare for working in co-operative education completed at least 30 hours. Objectives of research is exploratory factor analysis and confirmatory factor analysis of the vision about future and population in study is undergraduate students wishing to study co-operative education were studied at 6 government universities and 3 private universities total 1,000 and sample group 427 students in the cooperative education program in level of year 3rd - 4th. Finally structural analysis and examine of the visions about future. The researcher used a questionnaire that was able to measure and assess visions about future before students go to work cooperative education. Result of second-order confirmation factor analysis is consistent with empirical data χ2 = 310.537, df = 140, p = 0.000, χ2 /df = 2.218, CFI = 0.959, TLI = 0.950, RMSEA = 0.050, SRMR = 0.038. This discovery researchers hope that it will be the key to sustainable development of the human resource development platform in co-operative education courses that comes from the improvement and development of strategic ideas shared between academia and entrepreneurs. Meanwhile, students in the cooperative education program have already passed the training on the platform cooperative education students will be able to determine career paths and reduce of expect the establishment.